PKM Melalui Pelatihan Menyusun Laporan Penelitian Tindakan Kelas - Farah Pahrunnisa; Santi Dwi Handayani; Sherly Damayanti Fazrin (Rengganis Jurnal Pengabdian Masyarakat, 2023)
The competency to conduct Classroom Action Research for elementary school teachers is a very importantpedagogical competency that must be mastered as one of the teacher's professional competencies. However,in reality these competencies are still poorly understood and mastered by educators, especially teachers atthe elementary school level. Even when they have to make PTK reports, the teachers experience difficulties.To help teachers overcome their difficulties, we, students of the STKIP Kusuma Negara Bekasi in elementaryschool teacher education study program, have carried out a Community Service and Empowerment activityentitled "PKM Melalui Pelatihan Menyusun Laporan Tindakan Kelas Bagi Guru". This PKM activity aims toimprove the competence of elementary school teachers in conduct PTK and provide knowledge on how to makePTK reports, especially for teachers at the elementary school level. This PKM activity was carried out duringthe Covid-19 pandemic, so it was carried out boldly by utilizing virtual space using the Zoom Meetingapplication. This activity was carried out on 07 January 2023. The first meeting was filled with provision ofknowledge for participants regarding class action assessment reports, which then participants made PTKreports based on the format presented by previous speakers.